Strengthening women’s access to rural energy sources and technologies in Ethiopia: From research to action - Arega, Tiruwork; Ringler, Claudia (CGIAR, 2024)
A NEXUS Gains workshop held in Addis Ababa, Ethiopia explored entry points to strengthen women’s access to energy in rural areas